2022
DOI: 10.1049/cth2.12336
|View full text |Cite
|
Sign up to set email alerts
|

A parametric design method of observer‐based state feedback controller for quasi‐linear systems

Abstract: This paper designs an observer‐based feedback controller for quasi‐linear systems when the entire state vector is unavailable for measurement. First, based on the solution of a type of generalised Sylvester equations, general complete parameterisation of the full‐order observer is proposed. Second, the traditional separation principle is applied to the quasi‐linear systems. In other words, the design of a state feedback and the design of a state observer can be carried out independently. Further, general compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The premise of calculating gradient vector J ( i ) is to find e ( k ) / θ r and u ( k ) / θ r . Considering the structure shown in Figure 3, the state space expression of the controller (Gu et al, 2022) that can make the system stable is…”
Section: Design Of Dynamic Compensator Based On Gradient Estimatormentioning
confidence: 99%
“…The premise of calculating gradient vector J ( i ) is to find e ( k ) / θ r and u ( k ) / θ r . Considering the structure shown in Figure 3, the state space expression of the controller (Gu et al, 2022) that can make the system stable is…”
Section: Design Of Dynamic Compensator Based On Gradient Estimatormentioning
confidence: 99%
“…The estimate then serves as a substitute for non-measured signals, and it is then used by the control law as in [20] where the authors have addressed the trajectory tracking problem using saturated proportional-derivative (PD) control laws and disturbance compensation, in addition to an observer-based attitude tracking control that has been established in a separate design phase. The same procedure has been exploited in [21], where the authors have used the solution of a type of generalized Sylvester equation to parameterize a fullorder observer-based controller for a quasi-linear system. Moreover, the authors have demonstrated the validity of the separation theorem since they have considered perfectly known time-varying parameters and state values.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, as an important means of control, eigenstructure assignment for normal systems (Li and Lam, 2016; Yu and Duan, 2009), descriptor systems (Duan and Patton, 1997), and descriptor quasi-linear systems (Gu and Zhang, 2020, 2021; Gu et al, 2019) have become the focus of many scholars and been applied in related practical fields (Wang et al, 2022). In addition, many other problems of control system design have been solved effectively by using eigenstructure assignment theory (Gu and Wang, 2022; Gu et al, 2022a; Padula et al, 2021).…”
Section: Introductionmentioning
confidence: 99%